2012
DOI: 10.5817/cpr2012-2-11
|View full text |Cite
|
Sign up to set email alerts
|

Epilithic lichens and their morphological adaptations to the conditions of the White and Barents Seas coast (Russian Arctic)

Abstract: This study was supported by the Federal Program "Scientific and scientificpedagogical stuffs of innovative Russia" (SK 14.740.11.0300) and the work is executed with the financial supports of grant No. 5.5829.2011 AVCP, grant GK 14.740.11.0300 within the limits of FCP, grant from RFBR No. 12-04-01008-a. The author thanks Irina Urbanavichene and Vyacheslav Khanin (BIN RAS staff) for their help in carrying out biochemical analysis. Moreover the author thanks colleagues Eugenia Markovskaya and Liudmila Sergienko f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Similar to other researchers, determination of lichen zones was based on tidal rhythm, the presence of marker species, and structure of lichen communities additionally. From zone 1 to 4 (from the waterline to land), the structure of the lichen community changes from simple mono-species groups (e.g., Verrucaria ceuthocarpa or Hydropunctaria maura in zone 1) to complex multispecies groups, which include lichens of different life forms (mainly non-halophytic species in zone 4) (Sonina 2012).…”
Section: Marine Lichensmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to other researchers, determination of lichen zones was based on tidal rhythm, the presence of marker species, and structure of lichen communities additionally. From zone 1 to 4 (from the waterline to land), the structure of the lichen community changes from simple mono-species groups (e.g., Verrucaria ceuthocarpa or Hydropunctaria maura in zone 1) to complex multispecies groups, which include lichens of different life forms (mainly non-halophytic species in zone 4) (Sonina 2012).…”
Section: Marine Lichensmentioning
confidence: 99%
“…Due to larger diversity of habitats, six types of ecotopes were identified within these zones, which were inhabited mainly by eurybiont species. Sonina (2012Sonina ( , 2014, based on the analyzed literature as well as on the pairwise comparison of partial lichen flora in the zones on the coasts of the Barents and White Sea, suggested that the lichen cover of the coasts in the lichen zone 1 can be attributed to the azonal type of lichen flora (Table 1).…”
Section: Marine Lichensmentioning
confidence: 99%
See 2 more Smart Citations
“…On rocky shores a variety of interacting factors across this gradient (e.g. salinity (Grube & Blaha 2005;Delmail et al 2013), light (Sonina 2012), grazing (Higgins et al 2015) and water availability (Kranner et al 2008)) have led to the formation of lichen 'zones'. These zones correspond to distinctive coloured bands that begin at the top of the regularly submerged intertidal (black) and pass through parts of the shore exposed to regular sea spray/splashing (orange), to the upper zone that is influenced only by sea spray/splashing during storms (grey), before extending to fully terrestrial (i.e.…”
mentioning
confidence: 99%